Chasing on the way of cancer immunotherapy - Wu, Licun (Journal of Thoracic Disease; Vol 6, No 6 (June 26, 2014): Journal of Thoracic Disease, 2014)
I would like to share my experience of research in the following story. Based on my background regarding multiple directions in the field of cancer research including antiangiogenesis therapy, specific inhibitors of cancer cell repopulation between cycles of chemotherapy, and immunotherapy, I personally think the most promising approach to cure cancer might be through modulation of the immune system based on my research experience in past two decades.